David Coffey Reshaping Traditional Theology - Crittenden, Paul (2018)
The article seeks to locate the genealogy of David Coffey's systematic theology in his original search for a unified account of grace. This led to the recovery of early but forgotten ways of thinking about the central doctrines of the Trinity and Christology related especially to the role of the Holy Spirit in the Incarnation. Coffey's Spirit Christology, based on the Synoptic Gospels and patristic reflection, complements the traditional Christology of Chalcedon in ways that throw light on Christ's humanity and the redemptive character of his death and resurrection. It also grounds a theology of grace, Christian anthropology, death and resurrection, the Church, and the salvation of unbelievers. Coffey is a prominent Australian theologian and the discussion of his thought is set within a brief account of the development of theological studies in the Australian context.
Keywords: Christian Anthropology; David Coffey; Spirit Christology; Trinity; Grace; Resurrection; Salvation; theology in Australia